PENGGUNAAN ZAT PENGATUR TUMBUH (ZPT) ALAMI DAN PENGARUH LAMA PERENDAMAN UNTUK PERTUMBUHAN STEK PUCUK PULAI (Alstonia scholaris) - Asit, Avelina M. B. Un; Seran, Wilhelmina; Pellondou, Mamie E. (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2022)
Pulai (Alstonia scholaris) is one type of forestry plant that has many benefits and grows fast and has a wide distribution almost all over Indonesia. Vegetative propagation by cutting shoots becomes one of the alternatives to propagation of Pulai plants. Factors that are known to affect the success of plant propagation through cuttings shoots are Growing Regulatory Substances (PGRS) and the length of immersion. This research was conducted to find out the use of natural ZPT and the long-time influence of immersion for the growth of Pulai cuttings. The research method uses a Complete RandomIzed Design using a 2 (two) factor factor, namely the first factor, among others, natural PGRS consisting of 3 levels, namely aquades (control), PGRS Coconut Water and PGRS Onion Extract and the second factor, among others, the length of immersion consisting of 4 levels, namely Long Immersion 4 Hours, 6 Hours, 8 Hours, and 10 Hours. The results showed that the natural PGRS use treatment and combination of different treatments were not noticeable to the number of leaves, the length of the primary root, the length of the shoot, the length of the buds, the period of bud appearance and the percentage of life, while the length of immersion differed markedly from the number of leaves and differed in unreality over the length of the primary root, the length of the shoot, the period of bud appearance and the percentage of life of alstonia scholariscuttings. The use of PGRS coconut water (A1) has the highest average on the parameters of leaf count, length of buds, period of appearance of buds and percentage of life and PGRS of onion extract (A2) has the highest average on the primary root length parameter, while the highest average immersion length treatment is found at the length of immersion for 4 hours (B1).